Robust scheduling on a single machine usinge time buffers - Dirk Briskorn; Joseph Leung; Michael Pinedo (Universität Kiel, Institut für Betriebswirtschaftslehre, 2008)
This paper studies the allocation of buffer times in a single machine environment. Buffer times are a common tool to protect the schedule against disruptions such as machine failures. We introduce new classes of robust machine scheduling problems. For an arbitrary scheduling problem 1|ß|y, prmt ∉ ß, we obtain three corresponding robust problems: maximize overall (weighted) buffer time while ensuring a given schedule's performance (regarding y), optimize the schedule's performance (regarding y) while ensuring a given minimum overall (weighted) buffer time, and finding the trade off curve regarding both objectives. We outline the relationships between the different classes of problems and the corresponding underlying problem. Furthermore, we analyze the robust counterparts of three fundamental problems.
Keywords: 650; Single machine scheduling; robustness; buffer time allocation; Scheduling-Verfahren; Robustes Verfahren; Theorie